1989
DOI: 10.3168/jds.s0022-0302(89)79298-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein Percentage and Degradability on Performance of Lactating Cows During Moderate Temperature

Abstract: Sixty high producing Holstein cows (15/treatment) averaging 157 d postpartum were offered the following diets: high protein (18.5%), high rumen degradability (60%); high protein (18.0%), medium degradability (41%); medium protein (15.4%), high degradability (61%); medium protein (15.0%), medium degradability (46%). All diets contained 32% corn silage, 15% alfalfa haylage, and 10% whole cottonseed. Degradabilities were determined by the ficin method and were lowered by replacing soybean meal with meat and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…Also, as the study was conducted in hot ambient temperature (ranging from 28 to 36 ºC) and cows were subjected to moderate to severe heat stress. A reduction of DMI might have been the result of a higher amount of RDP (Higginbotham et al, 1989;Huber et al, 1994). Because of a similar percentage of OM between treatments (Table 1), intake of OM followed the same pattern as DMI.…”
Section: Resultsmentioning
confidence: 86%
“…Also, as the study was conducted in hot ambient temperature (ranging from 28 to 36 ºC) and cows were subjected to moderate to severe heat stress. A reduction of DMI might have been the result of a higher amount of RDP (Higginbotham et al, 1989;Huber et al, 1994). Because of a similar percentage of OM between treatments (Table 1), intake of OM followed the same pattern as DMI.…”
Section: Resultsmentioning
confidence: 86%
“…Similar findings were reported by Chumpawadee et al (2006) and Vongsamphan and Wandapat (2004). Higginbotham et al (1989) found an increase of 2.6 mg/dL in BUN in cows fed isonitrogenous and isocaloric diets by increasing RDP (0.2 kg/d) from 58 to 65% of dietary CP.…”
Section: N Metabolismmentioning
confidence: 93%
“…Although milk protein concentration was not reported in that trial, in light of the difference of 62% in CP intake between groups, it is very likely that the increase in milk yield was associated with a concomitant reduction in milk protein production efficiency. Higginbotham et al (1989a) investigated the effect of CP level (18% vs. 15%) on milk yield of cows during mid lactation; the cows were maintained under mild heat conditions (daily maximum = 27°C). Milk yield was not affected by percentage of dietary protein, but milk protein efficiency was higher for the low protein diet.…”
Section: Introductionmentioning
confidence: 99%